The Effects of Electronic Commerce on the Financial Position in Saudi Stock Companies Passing through COVID-19 – Field Study on STC Company – - Alsalem, Kawthar Ali; Albogami, Sultan Aide (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aims to identify the effects of the activities of e-commerce activities, positively or negatively, on the financial statements of Saudi stock companies passing through Covid-19, by focusing on the balance sheet and income statements in the telecommunications sector in the Kingdom of Saudi Arabia, where the study was a field study on the Saudi Telecom Company STC. To achieve the objectives of the study, the descriptive analytical approach was used to analyze the financial statements of the study sample company, based on horizontal analysis and percentages as tools in this study. The study concluded that there is an effects of electronic commerce activities on the financial statements of the stock company: Saudi Telecom passing through Covid-19, and that the effects differ in terms of positive or negative from one element to another, and accordingly, the main hypothesis related to the financial statements was accepted after accepting the two sub-hypotheses.